In vitro effects of photobiomodulation applied to gingival fibroblasts cultured on titanium and zirconia surfaces and exposed to LPS from Escherichia coli - Pansani, Taisa Nogueira [UNESP]; Basso, Fernanda Gonçalves; de Souza Costa, Carlos Alberto [UNESP] (Springer Nature, 2020)
Photobiomodulation (PBM) therapy is used to stimulate cell proliferation and metabolism, as well as reduce inflammatory cytokine synthesis, which plays a main role in the long-term stability of implants. This study assessed the response of gingival fibroblasts cultured on titanium (Ti) and zirconia (ZrO2), submitted to PBM and exposed to lipopolysaccharide (LPS). Cells seeded on Ti and ZrO2 were irradiated (InGaAsP; 780 nm, 25 mW) 3 times, using 0.5, 1.5, and 3.0 J/cm2 doses, and exposed to Escherichia coli LPS (1 μg/mL). After 24 h, cell viability (alamarBlue, n = 8), interleukin 6 (IL-6) and 8 (IL-8) synthesis (ELISA, n = 6), and IL-6 and vascular endothelial growth factor (VEGF) gene expression (qPCR, n = 5) were assessed and statistically analyzed (one-way ANOVA, α = 0.05). Cell morphology was evaluated by fluorescence microscopy. Increased cell viability occurred in all groups cultured on Ti compared with that of the control, except for cells exposed to LPS. Fibroblasts cultured on ZrO2 and LPS-exposed exhibited reduced viability. PBM at 3.0 J/cm2 and 1.5 J/cm2 downregulated the IL-6 synthesis by fibroblasts seeded on Ti and ZrO2, as well as IL-8 synthesis by cells seeded on ZrO2. Fibroblasts seeded on both surfaces and LPS-exposed showed increased IL-6 gene expression; however, this activity was downregulated when fibroblasts were irradiated at 3.0 J/cm2. Enhanced VEGF gene expression by cells seeded on Ti and laser-irradiated (3.0 J/cm2). Distinct patterns of cytoskeleton occurred in laser-irradiated cells exposed to LPS. Specific parameters of PBM can biomodulate the inflammatory response of fibroblasts seeded on Ti or ZrO2 and exposed to LPS.
Keywords: Abutments; Fibroblasts; LPS; Photobiomodulation